Responsibilities of Type A Mental Hospitals for EscapedPsychiatric Patients During the COVID- 19 Pandemic - Sri Ariani; Herliyani Nor Hidayat; Adilia Bi Maya Antari; MokhamadKhoirul Huda (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aims to determine the form of responsibility for a mental hospital type A if a patient with a mental disorder (psychiatric patient) escaped from the hospital during the COVID-19 pandemic. Outpatients and inpatients with a mental disorder can escape from the hospital because they have disturbed-awareness. The pandemic conditions of the COVID-19 pandemic are hazardous to contract both patients and doctors, and health workers. There are some problems related to the burden of responsibility to the hospital or inpatient staff to psychiatric patients who escape from the hospital. The study concludes that the responsibility for psychiatric patients who escaped from the hospital includes three parties: the head of the hospital, the attending physician, and the health workers such as nurses.